A life-threatening case of TAFRO syndrome with dramatic response to tocilizumab, rituximab, and pulse steroids: The first case report in Latin America. Issue 13 (March 2017) - José, Fabio Freire; Kerbauy, Lucila Nassif; Perini, Guilherme Fleury; Blumenschein, Danielle Isadora; Pasqualin, Denise da Cunha; Malheiros, Denise Maria Avancini Costa; Campos Neto, Guilherme de Carvalho; de Souza Santos, Fabio Pires; Piovesan, Ronaldo; Hamerschlak, Nelson
Abstract: Rationale: This is the report of the first case of TAFRO syndrome (Thrombocytopenia, Anasarca, myelofibrosis, Renal dysfunction, Organomegaly) in Latin America. Patient concerns: The patient was a 61-year-old white woman of Ashkenazi Jewish descent, who presented with a history of 8 days of nausea, vomiting, and fever; severe pitting edema in both legs, ascites, splenomegaly, and palpable axillary lymph nodes. Diagnoses: Abdominal computed tomography (CT) showed bilateral pleural effusion and retroperitoneal lymph node enlargement. Interventions: Anasarca and worsening of renal function led to admission to the intensive care unit (ICU) with multiple organ failure, requiring mechanical ventilation, vasopressor medications, and continuous renal replacement therapy (CRRT). Diagnosis of TAFRO syndrome was made on day 18 after admission, based on clinical findings and results of bone marrow and lymph node biopsies. She was treated with methylprednisolone, tocilizumab, and rituximab. One week after the first tocilizumab dose, she had dramatic improvements in respiratory and hemodynamic status, and was weaned from ventilator support and vasopressor medications. Outcomes: After 2 weeks of therapy, CRRT was switched to intermittent hemodialysis. On day 46, the patient was discharged from the ICU to the general ward, and 3 months after admission, she went home. Lessons: Provided the interleukin-6 measurement is available, this approach is suggested in cases of TAFRO syndrome, in order to customize the treatment.